KAJIAN SEMANTIK TERHADAP MAKNA LEKSIKAL DALAM KUMPULAN PUISI PADAMU JUA KARYA AMIR HAMZAH - Novela, Sindi; Suhardi; Mustado, Maulida; Irawan, Dody; Musliha; Zaitun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the lexical meaning found in the poetry collection Padamu Jua by Amir Hamzah through a semantic approach. The problem addressed in this study is the use of various words with lexical meanings that contribute to the construction of meaning, atmosphere, and emotional expression in the poems. This study aims to identify, classify, and describe lexical meanings found in the poetry collection Padamu Jua based on word classes. This research employed a descriptive qualitative method. The data consisted of words and expressions containing lexical meanings found in the selected poems in Padamu Jua. Data were collected through reading, note-taking, and documentation techniques, while data analysis was conducted by identifying the relevant words, classifying them according to their word classes, determining their lexical meanings based on the Indonesian Dictionary (KBBI), and interpreting their contribution within the context of each poetic line and stanza. The findings indicate that lexical meanings are found in several word classes, including nouns, verbs, adjectives, adverbs, pronouns, and interjections. The lexical meanings contribute to the representation of love, longing, sadness, helplessness, nature, isolation, and loss. The study demonstrates that lexical meaning serves as an important foundation for understanding the meaning constructed in Amir Hamzah’s poetry before interpreting its broader symbolic and contextual meanings.